Acute and chronic toxicity study of Valeriana wallichii rhizome hydro-ethanolic extract in Swiss albino mice - Joseph, Lovelyn; Puthallath, Rejeesh Edavan; Rao, Sundarshanram Narayan (Asian Journal of Medical Sciences, 2015)
Aims and Objective: To evaluate acute and chronic (90 days) oral toxicity of Valeriana wallichii rhizome hydroethanolic extract in Swiss albino mice. Materials and Methods: Valeriana wallichii rhizome was subjected to extraction with Soxhlet apparatus, using ethanol (90%) + water (10%) mixture and dried withrotavapor. Phytochemical fingerprinting of the extract was done with LC/MS (Liquid chromatography–mass spectrometry). Limit Test for acute oral toxicity at 2000 mg/kg body weight was conducted according to OECD guideline no 425. Chronic 90 day oral toxicity study with three different dose groups (200, 600, 1800 mg/kg/body weight/day) with selected in life parameters (physical, behavioural) and post mortem parameters (haematological, biochemical, gross necropsy and histopathological) as per WHO guidelines for testing safety of herbs was conducted. Results: Acute toxicity: no signs of abnormality, morbidity or mortality were observed during 14 days of observation. Chronic toxicity: Significant differences between the treated and control groups were observed in the following parameters: Loss of Auditory startle, Aggressiveness (Control > treated), Nasal discharge, Dyspnoea. At necropsy, tracheitis was observed in 3 cases. Results from Photoactometer test indicates dose dependent increase in sedative property. Conclusion: From this work it could be concluded that Valerianawallcihii rhizome hydroethanolic extract didn’t exhibit mortality, morbidity or any other neurologic, hematologic or biochemical adverse effects apart from sedation which is extension of their known pharmacological activity, after single oral dose of 2000mg/ kg bw (14 days of observation) or after once daily 200mg/kg, 600mg/kg 1800mg/kg oral treatment for 90days in healthy adult Swiss albino mice. Asian Journal of Medical Sciences Vol.7(2) 2015 49-54